2011
DOI: 10.1007/s11418-011-0545-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of ginkgolide K against acute ischemic stroke on middle cerebral ischemia occlusion in rats

Abstract: Ginkgolide K, a natural platelet-activating factor receptor antagonist, was isolated from the leaves of Ginkgo biloba. However, little is known about its neuroprotective effect in ischemia-reperfusion (I/R)-induced cerebral injury. Hence, the present study was carried out to investigate the effect of ginkgolide K on neuroprotection and the potential mechanisms in the rat I/R model induced by middle cerebral artery occlusion (MCAO). The rats were pretreated with ginkgolide K 2, 4 and 8 mg/kg (i.v.) once a day f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The data were calculated using Eqs. (1)- (5), where E (%) represents the pharmacodynamics effect, while C 1 , C 2 , C 3 , C 4 and C 5 represent the plasma concentration of the five physiological indices (C 1 : SOD; C 2 : MDA; C 3 : Glu; C 4 : IL-6; C 5 : TNF-␣) (Ma et al, 2011). The mean efficacy-time profiles after oral administration of HLJDT aqueous extract were measured.…”
Section: Experimental Design and Biochemical Analysismentioning
confidence: 99%
“…The data were calculated using Eqs. (1)- (5), where E (%) represents the pharmacodynamics effect, while C 1 , C 2 , C 3 , C 4 and C 5 represent the plasma concentration of the five physiological indices (C 1 : SOD; C 2 : MDA; C 3 : Glu; C 4 : IL-6; C 5 : TNF-␣) (Ma et al, 2011). The mean efficacy-time profiles after oral administration of HLJDT aqueous extract were measured.…”
Section: Experimental Design and Biochemical Analysismentioning
confidence: 99%
“…On the basis of this fact, antioxidative agents have been shown to be neuroprotective. Previous studies demonstrated that strategies used to reduce oxidative neuronal injury should have beneficial effects in improving the outcomes of ischemic stroke (13,14). HO-1 is a phase II defense enzyme that possesses a potent antioxidative ability.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,[33][34][35] G biloba extract is believed to lessen oxidative stress through various molecular mechanisms including superoxide dismutase, malondialdehyde, nitric oxide, and nitric oxide synthase in cerebral ischemia/reperfusion models in rats. 36 In a different study, Liu et al 37 assessed the anti-inflammatory effects of G biloba on ischemia-reperfusion brain tissue in rats. They found that the permeability of the blood-brain barrier (BBB) was enhanced by the administration of G biloba extract.…”
Section: Discussionmentioning
confidence: 99%